2018
DOI: 10.1038/s41467-018-05217-1
|View full text |Cite
|
Sign up to set email alerts
|

A radical S-adenosyl-L-methionine enzyme and a methyltransferase catalyze cyclopropane formation in natural product biosynthesis

Abstract: Cyclopropanation of unactivated olefinic bonds via addition of a reactive one-carbon species is well developed in synthetic chemistry, whereas natural cyclopropane biosynthesis employing this strategy is very limited. Here, we identify a two-component cyclopropanase system, composed of a HemN-like radical S-adenosyl-l-methionine (SAM) enzyme C10P and a methyltransferase C10Q, catalyzes chemically challenging cyclopropanation in the antitumor antibiotic CC-1065 biosynthesis. C10P uses its [4Fe-4S] cluster for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 51 publications
(52 reference statements)
1
37
0
Order By: Relevance
“…Several reports have suggested that ET is always accompanied by H + -transfer (proton transfer) in biological systems [45][46][47][48]. To evaluate proton transfer with butein and (S)-butin, we used a PTIO • scavenging assay established by our team [49].…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have suggested that ET is always accompanied by H + -transfer (proton transfer) in biological systems [45][46][47][48]. To evaluate proton transfer with butein and (S)-butin, we used a PTIO • scavenging assay established by our team [49].…”
Section: Resultsmentioning
confidence: 99%
“…Liquid chromatogram—high resolution mass spectrum (LC‐HRMS) analysis of 5′‐dAo was performed on an Agilent 1200 series coupled with a 6530 Accurate‐Mass Q‐TOF mass spectrometer in positive mode using a reversed‐phase column (Agilent, 250 × 4.6 mM, 5 μM) based on the method described by Jin, Wu, Jian, Yuan and Tang (). The mobile phase comprised solvent A (0.1% formic acid in Milli‐Q water) and solvent B (0.1% formic acid in acetonitrile).…”
Section: Methodsmentioning
confidence: 99%
“…tants were then collected and dried in a rotary evaporator (CHRIST RVC 2-25 CD plus, CHRIST, Osterode, Germany) under vacuum at 30°C. The resultant pellet was resuspended in 40 μl of sterile double-distilled water.Liquid chromatogram-high resolution mass spectrum (LC-HRMS)analysis of 5′-dAo was performed on an Agilent 1200 series coupled with a 6530 Accurate-Mass Q-TOF mass spectrometer in positive mode using a reversed-phase column (Agilent, 250 × 4.6 mM, 5 μM) based on the method described byJin, Wu, Jian, Yuan and Tang (2018). The mobile phase comprised solvent A (0.1% formic acid in Milli-Q water) and solvent B (0.1% formic acid in acetonitrile).…”
mentioning
confidence: 99%
“…(f-j) Reproduced under the terms of CC BY 4.0 license. [135] Copyright 2018, The Authors, published by Springer Nature.…”
Section: Power Efficiencymentioning
confidence: 99%
“…[68] Recently, a new grating scheme that uses a superposition of hybrid second-and fourth-order Bragg gratings was reported to have a remarkable power efficiency (peak power of 170 mW and PSE of 993 mW A −1 ). [135] The additional fourthorder gratings were introduced to tailor the radiative efficiency of antisymmetric and symmetric band-edge modes at will as shown in Figure 9h and both of the modes become radiative in this sense. By carefully choosing the structure parameters, single-mode single-lobe emission was robust over the whole dynamic range and the performance enhancement was independent of the temperature (Figure 9i), similar to those of GPH lasers (Figure 9d).…”
Section: Power Efficiencymentioning
confidence: 99%